BENTUK DAN JENIS PUISI PRISMATIS DALAM KUMPULAN PUISI AIR KATA KATA KARYA SINDHUNATA - Fatimah, Siti (MALIH PEDDAS, 2013)
The use of the term is less commonly used prismatic poetry when its existence can not be covered or removed from the history of poetry in indonesia. Thus, it is necessary to do the analysis or in-depth study of the works which can be categorized into these types of poetry. The analysis is based on the problem of